Overuse in cancer care: do European studies provide information useful to support policies? - Roberto Grilli; Valentina Chiesa (BMC, 2018)
Abstract Health services overuse has been acknowledged as a relevant policy issue. In this study, we assessed the informative value of research on the quality of cancer care, exploring to what extent it is actually concerned with care overuse, thus providing policy-makers with sound estimates of overuse prevalence. We searched Medline for European studies, reporting information on the rate of use of diagnostic or therapeutic procedures/interventions in breast, colorectal, lung and prostate cancer patients, published in English between 2006 and 2016. Individual studies were classified with regards to their orientation towards overuse according to the quality metrics adopted in assessing rates of use of procedures and interventions. Out of 1882 papers identified, 100 accounting for 94 studies met our eligibility criteria, most of them on breast (n = 38) and colorectal (n = 30) cancer. Of these, 46 (49%) studies relied on process indicators allowing a direct measure of under- or overuse, the latter being addressed in 22 (24%) studies. Search for overuse in patterns of care did not increase over time, with overuse being measured in 24% of the studies published before 2010, and in only 13% of those published in 2015-2016. Information on its prevalence was available only for a relatively limited number of procedures/interventions. Overall, estimates of overuse tended to be higher for diagnostic procedures (median prevalence across all studies, 24%) than for drugs, surgical procedures or radiotherapy (median overuse prevalence always lower than 10%). Despite its increasing policy relevance, overuse is still an often overlooked issue in current European research on the quality of care for cancer patients.